2007
DOI: 10.1525/as.2007.47.3.415
|View full text |Cite
|
Sign up to set email alerts
|

Prime Ministerial Popularity and the Changing Electoral Fortunes of Japan's Liberal Democratic Party

Abstract: This article explores the impact of prime ministerial popularity on the changing electoral fortunes of Japan's Liberal Democratic Party (LDP). We show that the popularity of the Japanese prime minister exerted a modest but definite impact on aggregate vote shares captured by the LDP throughout the postwar period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…13. The prime minister's popularity also affects elections, perhaps through perceptions of the LDP (Patterson and Maeda, 2007). 14.…”
Section: Discussionmentioning
confidence: 99%
“…13. The prime minister's popularity also affects elections, perhaps through perceptions of the LDP (Patterson and Maeda, 2007). 14.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on the recent elections in Japan suggests that party labels and the leadership's popularity now signiicantly inluence candidates' electoral fortunes (McElwain 2012;Patterson and Maeda 2007) and clientelism is now being replaced by programmatism (Rosenbluth and Thies 2010). Furthermore, in 2009 Japan had a government turnover through elections for the irst time in more than 60 years, because the combination of the DPJ's potential and disillusionment with the LDP government's policy performance convinced most swing voters: a poll on the 2009 turnover, for example, showed that 61.2% of voters thought party reputations were important in making voting decisions, compared to 29.0% who considered individual candidates' personal traits as important (Akarui Senkyo Suishin Kyōkai 2010).…”
Section: Kuniaki Nemoto and Chia-hung Tsaimentioning
confidence: 99%
“…A theory of electoral systems predicts that the move from SNTV to MMM should produce a trend away from personal politics and toward party-centered politics. The literature on the recent elections in Japan suggests that party labels and the leadership's popularity now signiicantly inluence candidates' electoral fortunes (McElwain 2012;Patterson and Maeda 2007) and clientelism is now being replaced by programmatism (Rosenbluth and Thies 2010). Furthermore, in 2009 Japan had a government turnover through elections for the irst time in more than 60 years, because the combination of the DPJ's potential and disillusionment with the LDP government's policy performance convinced most swing voters: a poll on the 2009 turnover, for example, showed that 61.2% of voters thought party reputations were important in making voting decisions, compared to 29.0% who considered individual candidates' personal traits as important (Akarui Senkyo Suishin Kyōkai 2010).…”
Section: Kuniaki Nemoto and Chia-hung Tsaimentioning
confidence: 99%